2020
DOI: 10.1038/s41598-020-64199-7
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid 159 of the envelope protein affects viral replication and T-cell infiltration by West Nile virus in intracranial infection

Abstract: West Nile virus (WNV) is an important cause of viral encephalitis in birds and animals, includinghumans. Amino acid 159 of the envelope (E) protein is reportedly implicated in the different levels of neurovirulence in mice infected with WNV NY99 or Eg101. We investigated the role of amino acid 159 of the E protein in the pathogenesis of WNV infection. We produced recombinant WNV with the structural proteins of the NY99 or Eg101 strain (NY-WT or EgCME-WT) and mutant viruses with substitutions of amino acid 159 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…A recent study by Kobayashi et al [111] supports this scenario. WNV recombinants between the highly virulent lineage 1 strain NY99 (V159) and the less virulent Eg101 (I159) strain were generated but did not show any significant differences in in vitro cultures or in C57BL/6 mice inoculated intraperitoneally.…”
Section: E Proteinmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study by Kobayashi et al [111] supports this scenario. WNV recombinants between the highly virulent lineage 1 strain NY99 (V159) and the less virulent Eg101 (I159) strain were generated but did not show any significant differences in in vitro cultures or in C57BL/6 mice inoculated intraperitoneally.…”
Section: E Proteinmentioning
confidence: 86%
“…In contrast, following the intracranial inoculation of mice, viral replication in the brain was higher for EgCME-E-I159V than for the parental strain EgCME. The mutation also increased levels of CD3+ and CD8+ T cells in the brain, suggesting that residue 159 of the E protein modulates WNV pathogenicity by influencing both viral replication and T-cell recruitment [111].…”
Section: E Proteinmentioning
confidence: 98%
“…Goshawks and kestrels can in fact be considered either migrant or resident birds. Unfortunately, it was not possible to check the carcasses, and eventually make out the bird behavior from wing, claw, and feather characteristics [74][75][76]. In support of the re-introduction of WNV-L1 is the lack of detection for consecutive years by the national surveillance program, which has been in place since 2002, and has been drawn to detect virus circulation early.…”
Section: Discussionmentioning
confidence: 99%
“…A threonine residue was observed at the 249 position in the strain MW627239, as well as in JF719065 and MW835362, circulating in Italy in 2008 (jay) and 2011 (owl), and in JF719069 and MT863559, circulating in Spain (horse) and France (human) in 2010 and 2015, respectively. Furthermore, the amino acid valine at the residue 159 of the E protein is considered a determinant of WNV neurovirulence, influencing viral replication and pathogenesis, and being involved in WNV infection and T-cell infiltration in the brain [75]. This amino acid is observed in the isolate NC009942, circulating in the USA in 1999, but not in the Italian and European strains, all characterized by isoleucine at this residue position.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of WN-IS98 and WN-IT08 genomes revealed 22 non-synonymous mutations, including E-V159I, also found on IS98-NS1, and NS4B-E249D. Kobayashi et al (2020) , demonstrated that E-I159V increased virulence in a mouse model. Here, the attenuated phenotype of WN-IT08 in mammals could be due to the E-V159I or the NS4B-E249D mutations, as well as to other modifications discussed earlier.…”
Section: Discussionmentioning
confidence: 96%